2017
DOI: 10.1016/j.jenvp.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Coupling social norms and commitments: Testing the underdetected nature of social influence

Abstract: Coupling social norms and commitments: Testing the underdetected nature of social influence 1.1 Introduction The onslaught of diverse and pressing environmental problems-from losses of natural habitat, species, and potable water, to a changing climate and a rapidly growing human population-necessitates empirically derived solutions. Because environmental problems chiefly stem from human behavior, environmental psychologists have much to contribute as specialists in the development and assessment of pro-environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 37 publications
5
33
0
2
Order By: Relevance
“…Study 2 explored whether a simple normative stimulus is sufficient enough to affect the observers' values, moral, and social norms. As expected, no changes were observed, thus further supporting the idea that norms affect intentions and behaviors directly [12,48] and their effects are not apparent to the observer [15,16]. Results suggest that behavioral change or at least intention to change can occur under normative stimulation, but any shifts in internalized values or norms need repeated behaviors to form reliable patterns.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Study 2 explored whether a simple normative stimulus is sufficient enough to affect the observers' values, moral, and social norms. As expected, no changes were observed, thus further supporting the idea that norms affect intentions and behaviors directly [12,48] and their effects are not apparent to the observer [15,16]. Results suggest that behavioral change or at least intention to change can occur under normative stimulation, but any shifts in internalized values or norms need repeated behaviors to form reliable patterns.…”
Section: Discussionsupporting
confidence: 68%
“…That is why following social norms functions as heuristics for behavior, having informational social influence and reducing the cognitive load when deciding upon an action. Moreover, social norms are rarely perceived by the observer as influencing one's behavior [15,16], making them a key component in successful public service announcements (PSAs), as they are not seen as pressuring one into behaving.…”
Section: Introductionmentioning
confidence: 99%
“…152) and have metaphorically been described as navigation tool steering behavior in a socially appropriate direction (Morris et al 2015). Past research has shown that social norms can be used to promote a number of pro-environmental behaviors such as littering prevention (Cialdini et al 1991;De Kort et al 2008), sustainable transportation (Kormos et al 2015), recycling (Schultz 1999), and water conservation (Richetin et al 2016;Schultz et al 2016;Jaeger and Schultz 2017). Past studies have also showed that social norms can be applied to promote energy conservation in both public (Bator et al 2014;Bergquist and Nilsson 2016;Dwyer et al 2015;Oceja and Berenguer 2009) and residential settings (Allcott 2011;Nolan et al 2008;Schultz et al 2007;Schultz et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of normative influence is often moderated by other psychological variables. For example, stating a commitment to save water before receiving normative information about water conservation promotes long-term water saving (Jaeger and Schultz 2017). Similarly, recent meta-analytic reviews suggest that the effect of social influence on sustainable behavior is conditional (Abrahamse and Steg 2013;Fischer 2008).…”
Section: Introductionmentioning
confidence: 99%
“…O conceito de "comportamento pró-ambiental" pode ser entendido como algum comportamento que beneficia o meio ambiente, melhora a qualidade ambiental, ou que de forma consciente prejudica o meio ambiente o mínimo possível 7,8 . Investigações sobre quais fatores são determinantes para a promoção de comportamentos próambientais, entendidos como comportamentos que visam à proteção ou diminuição de danos ao ambiente, têm sido recorrentes e um dos principais focos da psicologia ambiental nos últimos anos 9,10 .…”
Section: Comportamento Pró-ambientalunclassified